Impact of Sn doping on the hydrogen detection characteristics of ZnO thin films: Insights from experimental and DFT combination - El khalidi, Zahira; Daouli, Ayoub; Jabraoui, Hicham; Hartiti, Bouchaib; Bouich, Amal; Marí Soucase, Bernabé; Comini, Elisabetta; Munasinghe Arachchige, Hashitha M.M.; Fadili, Salah; Thevenin, Philippe; Kamal, Abderrafi; Hasnaoui, Abdellatif; et al. (Applied surface science, 2022)
[Display omitted] •ZnO gas sensors were successfully fabricated by a cost-effective spray pyrolysis.•The addition of Sn reduced the grain size for better adsorption of gas molecules.•Sn-doped ZnO showed the highest response under H2 with 200 at 500 ppm. The development of efficient chemical sensors based on semiconductor oxides is a major challenge. Low-cost equipment fabrication with a high sensor response towards H2 was the aim of our work. Chemical sensors were elaborated using zinc oxide, aluminum- and tin-doped zinc oxide. The samples were synthesized with a cost-effective chemical spray pyrolysis technique. Sn-doped ZnO response to hydrogen gas is the highest followed by ZnO and Al-doped ZnO, with a high sensitivity reaching 200 at 500 ppm, for 400 °C. DFT calculations revealed that O2 is strongly adsorbed on the ZnO-Al surface, resulting in the cancellation of the electrical conductance. Consequently, the approaching H2 gas will not possess sufficient energy to extract the strongly adsorbed oxygen from the surface, and no trapped electrons can be released back to the surface. In contrast, DFT calculations highlighted the potential of ZnO and Sn-doped ZnO to be used as hydrogen gas sensors. Charge transfer analysis revealed that only a small release of the trapped electrons occurs on the pure ZnO surface (0.14|e|), compared to Sn doped ZnO, in which a full release of free electrons was observed, resulting in a more favorable response to H2 and confirming the experimental results.